Effect of Family-centered Empowerment Model on Self-care Behaviors of Patients with Multiple sclerosis - Farshid Mohammad Mousaei; Hamid Reza Zendehtalb; Masood Zare; Hamid Reza Behnam Vashani (Mashhad University of Medical Sciences, 2021)
Background: Self-care behaviors contribute greatly to the management of multiple sclerosis (MS) and the prevention of its complications. The family has a critical role to play in the adoption of these behaviors in these patients. The present study aimed to assess the effect of the family-centered empowerment model on the self-care behaviors of MS patients.Method: This experimental study was performed on 60 patients referred to the MS Clinic of Ghaem Hospital in Mashhad in 2020-2021. The subjects who met the inclusion criteria were non-randomly assigned to two groups of control and experimental. Data collection tools included the demographic information form and the Performance Assessment of Self-care Skills (PASS) which were completed before and one month after the intervention in both groups. The educational content was presented to the experimental group in eight 45-60 min sessions in accordance with the family-centered empowerment model, while the control group received the routine training. Data were analyzed in SPSS software (version 16) using independent t-test, analysis of variance, and Mann-Whitney test.Results: The majority of participants in the experimental and control groups were female, single, and hold a diploma. The mean total scores of self-care behaviors after the intervention were obtained at 38.86±6.24 and 42.20±6.17 in the control and experimental groups, respectively. After the intervention, the mean total score of self-care behaviors and their dimensions in the experimental group was significantly higher than that in the control group (P<0.05).Implications for Practice: Hugo point massage with ice is suggested to be used as an available, efficient, and cost-effective method before arterial blood sampling.